Learning is the key twenty-first century skill. Issue 2 (2nd July 2016) - Kuhn, Deanna
ABSTRACT: Why are some people more effective learners than others? Despite the centrality of learning to life success, solid, comprehensive answers to this question do not yet exist. Global ability constructs do not provide adequate answers, and the case is made here for the need to go beyond them to closely examine the learning process itself and the multiple skills and dispositions that contribute to it. Only equipped with such knowledge can we understand individual differences in learning and be able to use this understanding to help all students become better learners.